Correlation Between pH of Saliva and Dental Caries among Children of Rajshahi City - Ferdose, Jannatul; Shamsuzzaman, AK Mohammad; Alom, Md Shah; Tasnim, Anika; Rahman, Nahreen (TAJ: Journal of Teachers Association, 2020)
Background: The aim of the study was to assess the salivary pH in dental caries children. The study was carried out with the objective of evaluation of pH of saliva by pH scale among healthy and caries children. Materials & Methods: A hospital-based study was conducted in the Department of Microbiology of Rajshahi in collaboration with Dental unit, Rajshahi Medical College Hospital, Rajshahi for a period between January to December 2017. All the cases were purposively selected from whom salivary sample were collected to measure pH using a chair side test strip. pH paper was rolled over the saliva on slide. Compare the colour against the standard to obtain a measurement. Results: The present study suggests that there is a significant relation between salivary pH and caries. Conclusion: We hypothesize that low salivary pH are associated with a higher dental caries rate. TAJ 2020; 33(1): 31-34